1993
DOI: 10.1016/s0022-5347(17)36415-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age, Parity, Oral Contraception, Hysterectomy and Menopause on the Prevalence of Urinary Incontinence in Women

Abstract: The influence of age, parity, duration of previous oral contraceptive use, hysterectomy and menopause on the prevalence of urinary incontinence was evaluated by means of a postal questionnaire in women 46 to 86 years old who resided in the city of Göteborg, Sweden. A sample of 10,000 women from the 7 birth cohorts of 1900 to 1940 was obtained at random from the population register. The overall response rate was 74.6%. The prevalence of urinary incontinence increased (p < 0.001) in a linear fashion from 12.1% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
188
6
27

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(243 citation statements)
references
References 17 publications
20
188
6
27
Order By: Relevance
“…The number of pregnancies was not a statistically signi®cant risk factor between these groups of women (vaginal or Caesarean delivery). Parity [5,25] has previously been regarded in some studies as a risk factor, but the type of delivery was not speci®ed and only vaginal delivery has thus been regarded as a risk factor [38,41]. The methods of these studies were similar to the present [38,41].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The number of pregnancies was not a statistically signi®cant risk factor between these groups of women (vaginal or Caesarean delivery). Parity [5,25] has previously been regarded in some studies as a risk factor, but the type of delivery was not speci®ed and only vaginal delivery has thus been regarded as a risk factor [38,41]. The methods of these studies were similar to the present [38,41].…”
Section: Discussionmentioning
confidence: 82%
“…Thomas et al [15] de®ned UI as leakage at least twice a month, and reported a prevalence of 10%; with a similar de®nition, some [11] reported a prevalence of 58%. Thus the prevalence of UI is very variable according to its de®nition, and in some studies using the ICS de®nition [37] of UI (`a condition where involuntary leakage is a social or hygienic problem'), with no regard to the frequency or the quantity of urine lost [5,6,12,33], the reported prevalence was 12±44%.…”
Section: Discussionmentioning
confidence: 99%
“…No existen estudios en Chile que demuestren la importancia de esta alteración en las usuarias de establecimientos de atención primaria. Igualmente, hay abundante evidencia internacional sobre factores de riesgo que se asocian al desarrollo o presencia de IU 3,5,15,16,17 , entre los que se encuentran la edad avanzada 3,5,6,16 , el aumento del índice de masa corporal 18,19,20,21 , la diabetes mellitus 22 , los embarazos y partos 23,24,25,26 , la historia de histerectomía 26,28,29,30 , y el inicio de la menopausia 26,27 . El presente estudio busca caracterizar la IU y los factores asociados a ésta en las mujeres que consultan en una unidad de la mujer en atención primaria, para determinar su peso relativo y así poder destinar recursos para su prevención y tratamiento.…”
Section: A Incontinencia Urinaria (Iu) Definida Por Launclassified
“…Guarisi et al 7 found no change in the risk of SUI caused by smoking and BMI. 16 Even though hysterectomy can be considered a risk factor, 25 a recently published study that analyzed 23,792 nurses did not show such correlation. 26 However, a study involving 3,537 Taiwanese women between 25 and 59 years demonstrated that hysterectomy was the greatest risk factor among gynecological surgeries.…”
Section: Introductionmentioning
confidence: 98%